Utilisation of old, extensive pig breeds for yellow nutsedge (Cyperus esculentus) control - A non-chemical and appealing approach - Total, René; Schmid, Martina; Keller, Martina (Julius-Kühn-Archiv, 2022)
Yellow nutsedge (Cyperus esculentus) is a troublesome weed in Switzerland. It reproduces mainly by tubers, but also by seeds. Dormant tubers in the soil cannot be controlled with herbicides. Pigs are known to reduce yellow nutsedge infestation levels by rooting up and consuming tubers. We hypothesized, that old pig breeds would especially be suited for yellow nutsedge control, as they search more actively for feed in the soil than modern pig breeds. A field trial with old pig breeds (Turopolje and Mangalica) was carried out in a field infested with yellow nutsedge (2019-2020). The pigs stayed in the field for 8 months. Infestation levels were determined before and after the trial by counting C. esculentus plants at 50 monitoring sites in the field. In addition, soil samples were taken before and after the experiment. The samples were placed in the greenhouse and emerging yellow nutsedge shoots were considered as a measure of the tuber bank in the soil. After 8 months of pig grazing in the field, we observed significantly less yellow nutsedge plants at the monitoring sites. Yellow nutsedge infestation levels i.e. the tuber bank was significantly reduced by 90%. This reduction is higher than the ones achieved in previous experiments and reported in the literature. Grazing of old pig breeds could be a non-chemical and an appealing approach for the public to considerably reduce yellow nutsedge infestation levels in affected fields.